Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques